2017
DOI: 10.1074/jbc.m117.816256
|View full text |Cite
|
Sign up to set email alerts
|

CHC22 and CHC17 clathrins have distinct biochemical properties and display differential regulation and function

Abstract: Clathrins are cytoplasmic proteins that play essential roles in endocytosis and other membrane traffic pathways. Upon recruitment to intracellular membranes, the canonical clathrin triskelion assembles into a polyhedral protein coat that facilitates vesicle formation and captures cargo molecules for transport. The triskelion is formed by trimerization of three clathrin heavy-chain subunits. Most vertebrates have two isoforms of clathrin heavy chains, CHC17 and CHC22, generating two clathrins with distinct cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 38 publications
5
41
0
Order By: Relevance
“…Hence, this data suggests the possibility of a new, additional function of CLTC in the context of autophagy. Recent studies have demonstrated that CLTC exists in 2 isoforms, CHC17 and CHC22, and that these isoforms have different functions [30,31]. CHC17 binds to clathrin light chains (CLC) and AP2 at the plasma membrane for endocytosis, however CHC22 binds neither CLC or AP2 and has been described to aid in trafficking of SLC2A4/GLUT4 (solute carrier family 2 member 4) [32].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, this data suggests the possibility of a new, additional function of CLTC in the context of autophagy. Recent studies have demonstrated that CLTC exists in 2 isoforms, CHC17 and CHC22, and that these isoforms have different functions [30,31]. CHC17 binds to clathrin light chains (CLC) and AP2 at the plasma membrane for endocytosis, however CHC22 binds neither CLC or AP2 and has been described to aid in trafficking of SLC2A4/GLUT4 (solute carrier family 2 member 4) [32].…”
Section: Discussionmentioning
confidence: 99%
“…CHC22 has been implicated in distinct tissuespecific membrane traffic pathways consistent with its different biochemical properties and restricted tissue expression. While both CHC22 and CHC17 homotrimerize into triskelia that assemble to form latticed vesicle coats, the CHC22 coat is more stable and within cells, the two clathrins form separate vesicles (Dannhauser et al, 2017). CHC22 does not bind the clathrin light chain subunits associated with CHC17 or the endocytic AP2 adaptor that recruits CHC17 to the plasma membrane, while CHC22 interacts preferentially with the GGA2 adaptor compared to CHC17 (Dannhauser et al, 2017;Liu et al, 2001;Vassilopoulos et al, 2009).…”
mentioning
confidence: 99%
“…This insulin-responsive GLUT4 pathway is the dominant mechanism for clearing blood glucose into muscle and fat after a meal (5). In addition to their distinct tissue expression patterns and biological functions, the two clathrins segregate in cells and CHC22 does not bind the CLC subunits that associate with CHC17 clathrin, even though the CHC protein sequences are 85% identical (3,6). This remarkable biochemical and functional divergence has evolved since the occurrence of a gene duplication that gave rise to the two different clathrins, 510-600 MYA (2) during the emergence of chordates.…”
Section: Introductionmentioning
confidence: 99%
“…These pathways are conventionally associated with clathrin function and are mediated by clathrin in all eukaryotic cells (1). CHC22 clathrin is most highly expressed in human muscle and adipose tissue and forms separate CCVs that are not involved in endocytosis (3). Instead, CHC22 CCVs regulate targeting of the glucose transporter 4 (GLUT4) to an intracellular compartment where it is sequestered until released to the cell surface in response to insulin (4).…”
Section: Introductionmentioning
confidence: 99%